Mudharabah, Musyarakah, Murabahah, Financing to Deposit Ratio: Profitability with Non Performing Financing as a Moderating Variable - Wahyuda, Muhamad Ridho; Nawirah, Nawirah (Gorontalo Accounting Journal, 2025)
The purpose of this study was to ascertain how financing options such as mudharabah, musyarakah, murabahah, and FDR affected the profitability of Indonesian Islamic Commercial Banks with regulated NPF between 2017 and 2023. moderated at Indonesian Islamic Commercial Banks from 2017 to 2023 by NPF. Of the total samples collected from seven (seven) Islamic commercial banks, forty-nine were used as observation locations. The quantitative approach makes use of moderation analysis and panel data regression models for data analysis. The outcomes According to this study, FDR has no influence on profitability, while mudharabah, musyarakah, and murabahah have a partial impact. on financial success. NPF factors can moderate the association between mudharabah, musyarakah, and murabahah variables on profitability, but they are unable to moderate the relationship cannot moderate the relationship between FDR on profitability. profitability